2014
DOI: 10.5586/am.2003.017
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the abundance of cellulolitic fungi and selected soil properties

Abstract: The study conducted has revealed the general abundance of cellulolytic fungi in the soil is significantly correlated only with the phosphors content. The correlation with specific soil properties was found in the case of the genera <i>Humicola, Penicillium, Fusarium</i> and <i>Chrysosporium</i> of the 10 genera of these fungi isolated most often.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The development of these fungi as well as exclusively saprotrophic fungi was also encouraged by a high nitrogen and phosphorus content (Tab.1) from bird faeces, feathers and other animal substrates. Previous studies by Korniłłowicz (1989); Korniłłowicz-Kowalska et al (2003) showed that the development of Fusarium and cellulolytic fungi is stimulated by the presence of nitrogen and phosphorus in the soil.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The development of these fungi as well as exclusively saprotrophic fungi was also encouraged by a high nitrogen and phosphorus content (Tab.1) from bird faeces, feathers and other animal substrates. Previous studies by Korniłłowicz (1989); Korniłłowicz-Kowalska et al (2003) showed that the development of Fusarium and cellulolytic fungi is stimulated by the presence of nitrogen and phosphorus in the soil.…”
Section: Methodsmentioning
confidence: 97%
“…DiscUssion nutrient-specialised saprotrophic micromycetes, such as keratinolytic or cellulolytic fungi, in natural environments, e.g. in the soil, are distributed non-uniformly (Korniłłowicz-Kowalska, Bohacz 2002a;Korniłłowicz-Kowalska et al 2003). The uneven distribution of various physiological groups of fungal saprotrophs is conditioned by the dispersion of organic matter which is the source of food for the microorganisms.…”
Section: Methodsmentioning
confidence: 99%
“…Mycological analysis of nests included determination of overall number of fungi (mesophilic saprotrophic fungi) isolated on Martin (1950) culture medium in 26 °C. Other fungi were isolated as follows: mesophilic fungi (30 °C); fungi potentially pathogenic for human and animals (Sabouraud medium supplied with antibacterial antibiotics) (Dvorak and Otcenasek, 1969); thermophiles (45 °C, Martin and Sabouraud medium); fungi potentially phytopathogenic from Fusarium group (Nash and Snyder medium) (Kwasna et al, 1991) cellulolytic fungi (Waksman cellulose medium on Whatman paper) as the only carbon and energy source (Kornillowicz-Kowalska et al, 2003), chitinophilic fungi using native chitin as a substrate and keratinophilic fungi using native keratin of feathers as a substrate (Kornillowicz, 1993). Fungi, excluding chitin- and keratinophilic, were isolated with usage of plate dilution method.…”
Section: Methodsmentioning
confidence: 99%
“…As reported by Wichern et al [ 32 ], dead fragments of meadow sward, including roots, may account for up to 90% of rhizodeposits. Combined with the ability of Fusarium to degrade cellulose and other polysaccharides [ 15 , 21 ], this creates good nutritional conditions for the saprotrophic growth of these fungi. Abiotic factors supporting Fusarium growth in peat-muck soils include moisture (hydrogenic soils) and low pH.…”
Section: Discussionmentioning
confidence: 99%
“…These fungi are associated primarily with agroecosystems and their specific microorganisms [ 12 ]. Previous investigations of the ecology of Fusarium in arable mineral soils [ 13 , 14 , 15 , 16 , 17 , 18 ] demonstrated the “affinity” of the genus to the roots of crop plants and its preference for acidic soils with a low level of clay minerals. These fungi are regarded as playing an important role in the functioning of plant communities and the maintenance of biological activity in cultivated soils.…”
Section: Introductionmentioning
confidence: 99%